The Influence of Length of Service and Work Experience on Work Performance in Mediating Professionalism at PT. Darul Umroh Alharamain - Sadri, Ali; Azhmy, Muhammad Fauzan; Tamba, Muller (Cattleya Darmaya Fortuna, 2025)
This research was conducted at PT. Darul Umroh Alharamain. This study aims to determine and analyze the influence of length of service and work experience on employee work performance in mediating professionalism at PT. Darul Umroh Alharamain. The population in the study was at PT. Darul Umroh Alharamain with a population of 112 employees, the sample in this study was 112 respondents with a sampling technique using the saturated sample method. Data collection using a questionnaire. The data analysis technique in this study used the path analysis method. The results of the study showed that length of service has an influence on professionalism, work experience has an influence on professionalism, professionalism is able to mediate the influence of length of service on work performance, and professionalism is able to mediate the influence of work experience on work performance